PHYLOGENETIC RELATIONSHIPS AMONG WEST INDIAN XENODONTINE SNAKES (SERPENTES; COLUBRIDAE) WITH COMMENTS ON THE PHYLOGENY OF SOME MAINLAND XENODONTINES - Crother, Brian I. (Contemporary Herpetology, 1999)
The evolutionary relationships of the West Indian (W. I.) xenodontine snake assemblage has been considered as either monophyletic or paraphyletic. Allozyme data from protein electrophoresis were used to estimate the phylogeny of the W. I. xenodontine snakes. Forty-two species from 25 genera (mainland and W. I. taxa) were examined. The phylogenetic relationships were estimated using parsimony analyses with successive approximation weighting on the data coded two ways: (1) the allele as the character and (2) the locus as the character. The most parsimonious trees from both coding methods indicated a non-monophyletic W. I. xenodontine assemblage. Three W.I. groups were recovered in both coding methods: (1) Jamaican Arrhyton and Darlingtonia, (2) Uromacer and the Cuban Arrhyton, and (3) Alsophis, Ialtris, and the South American Alsophis elegans. The relationships of Hypsirhynchus, Antillophis and Arrhyton exiguum were unstable. Nomenclatural changes are recommended for Darlingtonia, Arrhyton, Ialtris and Alsophis.